2021
DOI: 10.1002/acr2.11344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training on Patient Self‐Assessment of Joint Counts in Rheumatoid Arthritis: A Systematic Review

Abstract: Objective. Patient self-assessed joint counts, if accurate and reliable, could potentially serve as a useful clinical assessment tool in rheumatoid arthritis (RA). This systematic review examines the effect of patient training on the inter-rater reliability of joint counts between patients and clinicians.Methods. The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search was performed in PubMed, Embase, Cochrane Library, and CINAHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…27 When the impact of educational programs on the outcomes of chronic pathologies such as RA is analyzed, factors such as socioeconomic status and level of schooling must be taken into account. Note that a recent systematic review by Tam et al, 28 showed that not all studies reported data on patients' baseline characteristics (including level of education, socioeconomic status, or ethnicity), and this could affect the reliability of joint counts done by patients. In this study, there were no statistically significant differences between groups 1 and 2 in terms of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…27 When the impact of educational programs on the outcomes of chronic pathologies such as RA is analyzed, factors such as socioeconomic status and level of schooling must be taken into account. Note that a recent systematic review by Tam et al, 28 showed that not all studies reported data on patients' baseline characteristics (including level of education, socioeconomic status, or ethnicity), and this could affect the reliability of joint counts done by patients. In this study, there were no statistically significant differences between groups 1 and 2 in terms of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse-led programs of patient self-assessment of joint counts and disease activity have previously shown short-term benefits, and it may be helpful to include tender and swollen joint counts in teleconsultation. 18,19 Since the evaluation of tender and swollen joints is challenging in teleconsultation, the use of patient-reported outcomes (PROs) could be one method of deciding which patients would be suited to a teleconsultation or a face-to-face consultation, while ensuring that disease activity is controlled and symptoms important to the patient are not missed. The Rheumatoid Arthritis Impact of Disease (RAID) score, which comprises 7 domains encompassing pain, fatigue, physical function, sleep, physical well-being, emotional well-being, and coping, may be an interesting candidate given its strong correlation with the DAS28.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, treatment change was proposed in only 13/143 (9%) during a telemedicine appointment in the patient cohort reported by Avouac et al 10 However, information regarding swollen joint counts (SJCs) was rarely documented, although it is known that patients can be trained to reliably self-report SJC and tender joint count (TJC). 11,12 Yet traditionally, following the treat-to-target paradigm, the need for treatment change or otherwise would be determined by in-person assessment of composite measures of disease activity. In the Avouac et al study, 10 had it not been for the subsequent face-to face reviews that confirmed the appropriateness of the clinical management recommendations during the telemedicine consultations, these data might have given rise to some nervousness regarding the potential to underestimate active disease and thereby miss the opportunity to intervene with an appropriate treatment change.…”
mentioning
confidence: 99%